Esej z vidika antične filozofije - Fridl, Ignacija J. (Primerjalna književnost, 2010)
This article proceeds from Montaigne's premise on the essay as a reflection of the Self. From today's perspective, it should be understood in the sense of focusing on the Self as the subject. However, if Montaigne's idea and Renaissance thought are interpreted from the historically reverse direction, from the perspective of the ancient human conception, especially from the philosophical viewpoint inherited from Socrates via Plato, then the perspective on the essay as a reflection of the Self can be understood such that the Self in the essay form determines the measure and limit of one's own existence through reflection on broader matters. From this perspective, the essay in the proper sense of the word cannot merely be a historical genre, but must be understood in the sense of "lived literature."
Keywords: Plato, 427-347 pr. n. št.; Montaigne, Michel de, 1533-1592; književnost; literature; antična filozofija; esej; jaz; subjekt